Keberlanjutan Bisnis dan Tanggung Jawab Sosial Perusahaan: Studi Kasus Midea Group dan Perbandingan dengan LG Group - Pratama, Pondi; Prakoso, Fransiskus Bayu; Pramudia, Hanisa; Adhyatmika, I Gusti Bagus Wiradharma; Arifin, Intan Putri Agung; Aryani, Tarina (Publikasi Indonesia, 2025)
This study discusses the implementation of Business Sustainability and Corporate Social Responsibility through a case study of Midea Group (China) and a comparison with LG Group (South Korea). With a qualitative case study approach, this study analyzes the sustainability strategies, business ethics, and implementation of the ESG (Environmental, Social, and Governance) framework of both companies based on the latest sustainability report and Fred R. David's analytical framework. The results show that Midea Group has demonstrated a commitment to environmental efficiency and technological innovation, but there is still room for improvement in terms of social inclusion and reporting transparency. On the other hand, LG Group displays a more comprehensive and strategic approach in the implementation of CSR and is superior in reporting and governance based on global standards. This study concludes that business sustainability is not just a compliance demand, but a strategic element in creating a long-term competitive advantage. Recommendations that Midea can make to improve the quality of Sustainability Report reporting through the adoption of international standards, expand the social impact of CSR programs, and strengthen sustainability governance as a step towards higher global competitiveness.